Rohstoffe - Menschen - Wissen Einblicke in die Ressourcengeschichte des historischen Tirols - Neuhauser, Georg; Taddei, Elena (Innsbrucker Historische Studien, 2024)
Access to, lack of and waste of resources are now more than ever the subject of debate and conflict. The ideas and practices of sustainability and the careful use of resources are increasingly fuelling scientific research, political discussions and the entire media world. Many of these modern discourses have grown historically and date back to well before our time. But what are resources anyway? Who recognises them and drives their use? How is a lack of certain resources recognised and overcome? The contributors to this volume have analysed these and other questions from the perspective of regional history, covering a period from the late Middle Ages to the 20th century. In spatial terms, the individual analyses focus on the area of historical Tyrol in its various forms as a county (Tyrol), crown land (Tyrol and Vorarlberg) and European region (Tyrol-South Tyrol-Trentino), i.e. on an area stretching from Kufstein in the north to Ala in the south.